Genomic landscape of extended-spectrum β-lactamase resistance in Escherichia coli from an urban African setting. (4th March 2017) - Musicha, Patrick; Feasey, Nicholas A.; Cain, Amy K.; Kallonen, Teemu; Chaguza, Chrispin; Peno, Chikondi; Khonga, Margaret; Thompson, Sarah; Gray, Katherine J.; Mather, Alison E.; Heyderman, Robert S.; Everett, Dean B.; et al.
Abstract : Objectives: Efforts to treat Escherichia coli infections are increasingly being compromised by the rapid, global spread of antimicrobial resistance (AMR). Whilst AMR in E. coli has been extensively investigated in resource-rich settings, in sub-Saharan Africa molecular patterns of AMR are not well described. In this study, we have begun to explore the population structure and molecular determinants of AMR amongst E. coli isolates from Malawi. Methods: Ninety-four E. coli isolates from patients admitted to Queen's Hospital, Malawi, were whole-genome sequenced. The isolates were selected on the basis of diversity of phenotypic resistance profiles and clinical source of isolation (blood, CSF and rectal swab). Sequence data were analysed using comparative genomics and phylogenetics. Results: Our results revealed the presence of five clades, which were strongly associated with E. coli phylogroups A, B1, B2, D and F. We identified 43 multilocus STs, of which ST131 (14.9%) and ST12 (9.6%) were the most common. We identified 25 AMR genes. The most common ESBL gene was bla CTX-M-15 and it was present in all five phylogroups and 11 STs, and most commonly detected in ST391 (4/4 isolates), ST648 (3/3 isolates) and ST131 [3/14 (21.4%) isolates]. Conclusions: This study has revealed a high diversity of lineages associated with AMR, including ESBL and fluoroquinolone resistance, in Malawi. The data highlight the value of longitudinal bacteraemia surveillance coupled with detailed molecular epidemiology in all settings, including low-income settings, in describing the global epidemiology of ESBL resistance.